The Case for 'Contributory Ethics': Or How to Think about Individual Morality in a Time of Global Problems. Issue 3 (1st September 2020) - Rieder, Travis N.; Bernstein, Justin
ABSTRACT: Many of us believe that we can and do have individual obligations to refrain from contributing to massive collective harms – say, from producing luxury greenhouse gas (GHG) emissions; however, our individual actions are so small as to be practically meaningless. Can we then, justify the intuition that we ought to refrain? In this paper, we argue that this debate may have been mis-framed. Rather than investigating whether or not we have obligations to refrain from contributing to collective action, perhaps we should ask whether we have reason to do so. However, this framing brings challenges of its own, and so we close by asking what problems are generated if we focus on these questions of 'contributory ethics'.